2012
DOI: 10.1007/s10753-012-9555-1
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 Activities, Biological Structure, and Source Along with Its Significant Role Played in Pathophysiology of Type I Diabetes Mellitus

Abstract: The etiology of the most autoimmune disorders is largely yet to be understood. However, major target antigens have been determined against some of clinically important molecules of human autoimmune diseases, such as insulin in type 1 diabetes mellitus (T1DM). T1DM is believed to be resulted from immune-mediated destruction of insulin-producing β-cells in pancreatic islets of Langerhans. Chemokines are small glycoproteins (weighing 8-10 kDa) that are chemotactive for a wide variety of cell types especially immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 72 publications
0
43
0
Order By: Relevance
“…However, an identification of the structural properties and mechanism of action of CXCL10 needs to be made if CXCL10 is to be used as a worthwhile therapeutic target for treatment of the aforementioned pathological conditions. CXCL10 was initially identified in human U937 cells (a histiocytic lymphoma cell line with monocytic characterization and origin) and from human placenta and spleen as an IFN-γ-inducible product [30]; mob-1 and crg-2 are the rat and mouse homologs of human chemokine CXCL10, and they share 70 and 78% amino acid homology with these proteins, respectively [31]. Like other members of the chemokine subfamily, CXCL10 is a small-molecular-weight protein (10 kDa) which was functionally described as an ‘inflammatory' chemokine.…”
Section: Cxcl10 Biostructure and Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, an identification of the structural properties and mechanism of action of CXCL10 needs to be made if CXCL10 is to be used as a worthwhile therapeutic target for treatment of the aforementioned pathological conditions. CXCL10 was initially identified in human U937 cells (a histiocytic lymphoma cell line with monocytic characterization and origin) and from human placenta and spleen as an IFN-γ-inducible product [30]; mob-1 and crg-2 are the rat and mouse homologs of human chemokine CXCL10, and they share 70 and 78% amino acid homology with these proteins, respectively [31]. Like other members of the chemokine subfamily, CXCL10 is a small-molecular-weight protein (10 kDa) which was functionally described as an ‘inflammatory' chemokine.…”
Section: Cxcl10 Biostructure and Functionsmentioning
confidence: 99%
“…External stimuli which affect CXCL10 and the intracellular events leading to its expression (adopted from Ahmadi et al [30]). Signals are initiated by receptor-ligand interaction, either involving growth factors or cytokines, and stress stimuli are illustrated.…”
Section: Cxcl10 Biostructure and Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The over-expression of MHC class-1 antigens leads to the production of several chemokines including RANTES and MCP-1 that attract MCs and other immune cells, which can be deleterious for the pancreatic β cells [19]. We previously reported that RANTES and MCP-1, which are part of the chemokine supergene family (8-to 10-kD proteins) inducible in a number of pathophysiologic processes, intradermally injected (10 ng/50 μl subcutaneously in the abdominal skin of rat) produce a strong inflammatory reaction, due to the recruitment of mast cells, showing that these chemokines are potent pro-inflammatory proteins with specific chemoattraction on inflammatory MCs [20].…”
Section: Introductionmentioning
confidence: 99%